Proteinase-activated receptor-2 modulates human macrophage differentiation and effector function. Issue 6 (December 2013) - Steven, Rachael; Crilly, Anne; Lockhart, John C; Ferrell, William R; McInnes, Iain B
Proteinase-activated receptor-2 (PAR-2) was shown to influence immune regulation; however, its role in human macrophage subset development and function has not been addressed. Here, PAR-2 expression and activation was investigated on granulocyte macrophage (GM)-CSF(M1) and macrophage (M)-CSF(M2) macrophages. In both macrophages, the PAR-2-activating peptide, SLIGKV, increased PAR-2 expression and regulated TNF-α and IL-10 secretion in a manner similar to LPS. In addition, HLA-DR on M1 cells also increased. Monocytes matured to an M1 phenotype in the presence of SLIGKV had reduced cell area, and released less TNF-α after LPS challenge compared with vehicle ( P  < 0.05, n  = 3). Cells matured to an M2 phenotype with SLIGKV also had a reduced cell area and made significantly more TNF-α after LPS exposure compared to vehicle ( P  < 0.05, n  = 3) with reduced IL-10 secretion ( P  < 0.05, n  = 3). Thus, PAR-2 activation on macrophage subsets regulates HLA-DR and PAR-2 surface expression, and drives cytokine production. In contrast, PAR-2 activation during M1 or M2 maturation induces altered cell morphology and skewing of phenotype, as evidenced by cytokine secretion. These data suggest a complex role for PAR-2 in macrophage biology and may have implications for macrophage-driven disease in which proteinase-rich environments can influence the immune process directly.